Using Inertial Measurement Units to Quantify External Load in Men's Singles Badminton Matches: Insights from Set Outcomes and Score Gaps. - Guo, Zhenxiang; Jiang, Leyi; Liu, Chunlong; Yang, Zhihua; Qin, Shenglei; Jiang, Dongting; Bao, Dapeng; Dai, Jin; Liu, Haoyang (Journal of Sports Science & Medicine, 2025)
Quantifying external load using kinematic variables from inertial devices provides crucial insights into player performance. This study analyzed load variables in men's singles badminton matches, differentiating between set outcomes (winners vs. losers) across different score gaps (0-5, 6-10, >10 points). Data were collected from 18 highly trained players (110 sets) using the Catapult Vector S7 microtechnology units, housed with a 100hz accelerometer, gyroscope and magnetometer. The results indicated that set winners exhibited a lower player load (estimated difference [ED] and 95% CI = -14.1 [-26.20, -1.78], p = 0.023), covered less distance (ED = -134.84 [-248.99, -17.01], p = 0.02), performed fewer explosive efforts (defined as the sum of high-intensity accelerations, decelerations, and changes of direction [COD]) (ED = -19.75 [-31.85, -7.33], p = 0.002), CODs (ED = -21.02 [- 34.18, -7.67], p = 0.003), and accelerations (ED = -7.03 [-13.16, -0.73], p = 0.03) than set losers. Notably, when the score gap was narrow (0--5 points), set winners performed more explosive efforts and CODs than set losers (adjusted p = 0.0412 and 0.0499, respectively). However, as the score gap widened (6--10 and >10 points), set winners exhibited fewer explosive efforts and CODs (all adjusted p < 0.05). Furthermore, when the score gap exceeded 10 points, set winners demonstrated a lower player load, covered less distance, and performed fewer right-side CODs (all adjusted p < 0.05). These findings suggest that winners generally have a lower external load in men's singles badminton matches. However, when opponents are evenly matched, on-court movement may play a pivotal role in determining the outcome.